Source separation of solid waste for recycling practice at household level in Johor and Selangor, Malaysia - Moh, Yiing Chiee (2017)
Beginning June 1st, 2016, source separation of solid waste for recycling practice is mandatorily enforced with compound taking effect at household level in Malaysia as part of the country's transformed strategy towards sustainable solid waste management. However, not all states in Malaysia share similar policy approach in introducing and sustaining the practice among households. Addressing that, this study evaluated source separation of solid waste for recycling practice from the perspectives of the main organizations and households in two of the most populated states that represent different policies of solid waste management in Malaysia, specifically Johor and Selangor. Based on purposive sampling, 19 lead officers representing solid waste management organizations in both states participated in the semi-structured interviews. Data derived from interview transcripts were analyzed and the interpretations were corroborated with the documents provided by participants. This study also conducted questionnaire survey involving randomly selected respondents from each area of jurisdiction under local authorities in both states. The sampling successfully gathered 589 respondents from Johor and 806 respondents from Selangor. This study also adopted Theory of Planned Behaviour (TPB) to provide a more nuanced view of the practice among households in both states. Based on the interviews, the overall management in Johor and Selangor were different in terms of expectations and organizational structure and system. However, participants revealed similar conflicts of interest between organizations and households in both states. Despite comparatively similar challenges in resources, personnel, and technicality, participants in Selangor encountered issues that were more apparent without specific regulatory instrument. As for households, majority were supportive of mandatory approach regardless of the type of policy implemented (U = 232134.5, z = -0.839, p = 0.402). Households' responses on perception towards solid waste, challenges faced, expectations, and willingness to participate were comparatively similar between both states. Meanwhile, attitude explained significantly more of the variance in behavioural intention for households in Johor (r= 0.56, p < 0.01) than in Selangor (r = 0.43, p < 0.01). Similarly, moral norm explained significantly more of the variance in behavioural intention for households in Johor (r = 0.70, p < 0.01) than in Selangor (r = 0.63, p < 0.01). Interestingly, there was also a statistically significantly difference in the strength of the correlation between attitude and moral norm for households in both states where attitude explained significantly more of the variance in moral norm for households in Johor (r = 0.77, p < 0.01) than in Selangor (r = 0.72, p < 0.01). Standard multiple regression were subsequently performed for cases of Johor and Selangor, which revealed that the inclusion of moral norm increased the predictiveness of TPB based on the results of three proposed models. Obtained principal component analysis results revealed attitude, moral norm, and behavioural intention loaded strongly on a single component, suggesting these components may not be separately considered. This also reaffirmed the unique association between attitude and moral norm on behavioural intention of households, despite under different policy approach. Meanwhile, the one-way between-groups multivariate analysis of variance results revealed that gender, age group, and education level do not play a defining attribute in determining households' overall behaviour in both states. The number of children in household, however, may have potential influence over households' moral norm under mandatory approach (Johor), F (2, 586) = 4.67, p = 0.010, partial eta-squared = 0.016 using a Bonferroni adjusted alpha level of 0.01. Conclusively, this study addressed pertinent issues and challenges within the existing solid waste management system in the context of source separation of solid waste for recycling practice at household level in Malaysia from multifaceted perspectives. In this context, this study also proposed and recommended a framework of planning and management, implementation, and evaluation based on the obtained qualitative findings and quantitative results.